Kitsch and Avant-garde Television in Blackpool (Peter Bowker, BBC, 2004) - Nicole Cloarec (Revue LISA)
As its American title, Viva Blackpool, indicates, BBC’s Blackpool originates in at least three glittering icons which epitomize the glitz and kitsch of Anglo-Saxon popular culture. Set in “Britain’s largest, busiest and best-publicised popular resort”, the six-episode television drama refers to the city’s attempts to create the “Las Vegas of the North” as well as to Elvis Presley’s famous song which opens the first episode. While mixing generic reference points such as the detective thriller, melodrama and the musical, Blackpool’s most notable achievement is its extensive and highly original use of popular songs. In a device reminiscent of Dennis Potter’s work, actors burst into song sequences and dance routines with their voice superimposed on the original, blurring the distinction between diegetic and non-diegetic origins and undermining all mimetic illusion. Reading Blackpool through the critical perspective of kitsch aesthetics allows one to pinpoint the ambivalence of its narrative and aesthetic choices. Thanks to the extensive use of generic conventions and iconic artefacts of popular culture, the serial drama builds up on their pre-existing emotional resonance while highlighting their artificiality through self-reflexive devices. Ultimately, Blackpool’s stylistic originality demonstrates the ability of television drama to provoke a dual mode of engagement, which combines the pleasure of immediacy while exposing it as artifice. In so doing, it proves that, contrary to what Walter Benjamin asserted, the use of kitsch can provide “emotional gratification” along with critical distance.